MAINSTREAMING PEACE AND SECURITY IN THE NIGER DELTA: RESOURCE CONTROL, ETHNIC NATIONALISM AND CONFLICT CESSATION IN A TURBULENT SYSTEM (Global Journal of Human-Social Science, 2012)
As a metaphor of collective resistance to the politically motivated assault by the majority nationalities on the economic rights of minority communities resource control expresses the exponential challenge to the politics of dispossession of oil producing communities in the federation of Nigeria The Nigerian federal system as incisively articulated in the protest literature embody the tyranny of the majority over hapless minority formations whose struggle for relevance constitute in generational terms a challenge to the coercive presence of the majority The phenomenological exploration of this theme of hegemony in the Nigerian federalism has found multiple expressions in the works of Saro-Wiwa Okonta and Douglas Otite Osaghae Agbese and Suberu
Keywords: Hegemony; federation; coercive presence; federalism